Croplands Quality Evaluation of Whole Tillage Layer Based on the Minimum Data Set in Jilin Province, China - Jinyao Yan; Kangning Xu; Dongming Du; Xinyu Jia; Wei Fan; Yao Liang; Dezhong Li; Ying Zhang; Jun Ren; Jianzhao Liu; Hongguang Cai (Agronomy)
The aim of this study is to accurately evaluate the quality characteristics of whole tillage cropland and deepen the knowledge of sub-tillage soil quality evaluation in Jilin Province, China. In this study, top-tillage and sub-tillage soil samples were collected from 185 maize continuous cropping areas in Jilin Province, and 12 physicochemical indexes (pH, cation exchange capacity (CEC), soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), total potassium (TK), available nitrogen (AN), available phosphorus (AP), available potassium (AK), sand, silt, and clay) were used to evaluate the whole tillage layer soil quality index (SQI). The results showed that the whole tillage soil physicochemical indexes in Jilin Province were generally above the moderate level, and nutrient contents increased from West to East among the regions. The minimum data set SQI (SQI-MDS) of the top-tillage and sub-tillage layers were 0.22–0.98 (0.46) and 0.23–0.93 (0.55), respectively. The suitable ranges of MDS parameters for reasonable tillage layers were as follows: top-tillage layer SOM ≥ 34.5 g kg−1, 31.5% ≤ sand ≤ 53.5%, AP ≥ 32.1 mg kg−1, and TK ≥ 15.18 g kg−1; sub-tillage layer 31.3% ≤ sand ≤ 51.2%, TN ≥ 1.48 g kg−1, 6.4 ≤ pH ≤ 7.1, and AK ≥ 157.6 mg kg−1. In summary, the SQI and evaluation indexes of the top-tillage and sub-tillage layers in different ecological zones are varied. It is necessary to adjust the evaluation index thresholds in combination with the actual conditions to establish a more accurate evaluation index system of the whole tillage soil quality.